THE LEADERSHIP OF KYAI ON IDIOSYNCRATIC PERSPECTIVE; AN INFLUENCE OF PERSONAL CHARACTERISTIC IN PESANTREN - Yudik Al-Farisi; Ahmad Nuvi (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2021)
The Kiai as the highest Leader in the pesantren, has a significant influence on the good and bad of the Pesantren. This study focuses on the privilege (idiosyncratic) of Kiai Abdul Hamid Wahid as the Leader of the Pesantren Nurul Jadid. These privileges can affect the performance of employees and management in carrying out their respective duties. The author conducts research using qualitative methods, with observation, interviews, and documentation. The discussion results show that idiosyncrasy, which includes the values, experience, and talents of Kiai Abdul Hamid Wahid, makes him a leader who has an enormous influence on the performance of employees and administrators well as in decision making at the Pesantren Nurul Jadid.